(3WHbGJ GdeLJgOjfs - (3GdJhbGOj GdESJGfHhdj GdYKeGfj GdMfaj, GHf ceGd HGTG, ceGd HGTG RGOg, TeS GdOjf, CMeO Hf SdjeGf Hf ceGd HGTG, (B940 (3g`s
(3ChdgG (B:s
(3GYde Cf GdabgGA Ydi SHYI WHbGJ GdChd (B( (3cPG(B) (3WHbI GdeLJgOjf aj GdTQY cGdCFeI GdCQHYI hef Sdc eSdcge aj JCSjS bhGYO GdCUhd hESfGO CMcGe GdaQhY Yf COdI GdCQHYI GdcJGH hGdSfI hELeGY GdCeI hGdbjGS Ydi MSH Jdc GdbhGYO ef ZjQ JbdjO dCMO aj GdaQhY hdG aj GdCUhds
(3BNQgG (B:s
(3GdSGHYI WHbI GdebdOjf GdPjf dG jbOQhf Ydi eG PcQ hdG jaQbhf Hjf GdYTH (B((3cPG(B) (3hGdSejf dG jjR Yf GdTeGd Yf Gdjejf (B((3cPG(B) (3Hd jLeYhf eG jLOhf cMGWH Gddjd bGdhG Hd dge cd Gdhjd GdMeO ddg ChdG hBNQG hXGgQG hHGWfGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 1 / 133s
(3eYLe GdeDdajf(B: 1 / 148s
(3cTa GdXfhf(B: 2 / 1106s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJGQjNs